PRINCIPALS, PRE-SCHOOL TEACHERS AND PARENTS’ VIEWS ON THE EFFECTIVENESS OF THE LIFE-FOCUSED FOREIGN LANGUAGE ACQUISITION PROGRAM WHICH IS DEVELOPED FOR PRE-SCHOOL AGED CHILDREN - USLU, Banu; CAGDAS, Aysel (The Eurasia Proceedings of Educational and Social Sciences, 2017)
The present study was carried out to determine the views and thoughts of school principals, teachers and pre-school children’s parents about the Life-Focused Foreign Language Acquisition Program (LFFLAP.) The research was carried out qualitatively. In order to collect the qualitative data, a semi-structured interview form, which was developed by the researcher, was used. The collection of qualitative data was between December 1, 2015 and February 19, 2016. Interviews were done with 38 participants. The participants were as follows: one principal, one assistant principal, four teachers and 32 parents. The qualitative data obtained in the study was analyzed by “content analysis” technique. Word Clouds Program was used to determine the relevant concepts and distributions that emerged during the interviews. As a result of analysis of various data obtained from parents, teachers, and the school principal and assistant principal in the study, positive opinions regarding the Life-Focused Foreign Language Acquisition Program were found. The themes that emerged during the interviews are as follows: active foreign language use, active transfer of foreign language, self-confidence in using foreign language, active interest/positive attitude towards foreign language, improvement in self-expression/pronunciation, sharing whatever is learned effectively, making progress actively in the foreign language and multiple experiences in foreign language learning (visual, auditory, etc.).